The Value of the Participation of Actors in the Technology Transfer Process: a Strategic Vector - A. S. Khvorostyanaya; M. K. Alimuradov (Управленческое консультирование)
Goal. In the modern economic system, a significant role is played by the development of new technologies, which are the driver of innovation. The changing nature of technology and knowledge transfer between the academic and industrial sectors is also a prominent area of study. However, there is no effective interaction system between researchers producing new technologies with commercialization potential and enterprises in the commercial sector, designed to enhance the innovative development of the economy. This article discusses the strategic meaning of the participation of various technology transfer market agents in the process of interaction between innovators and enterprises in the field of commercialization. A strategic approach to the main groups of participants and stakeholder analysis ensures high-quality ownership of the received technology and minimizes risks during the entire stage of the technology transfer implementation. A carefully verified description of technological capabilities in terms of their unique components and features allows the business to understand what might be the potential basis for its future competitive advantage.Methods. In this article, using such general scientific methods of cognition as analysis, synthesis and induction, we analyze the value orientations of a technology transfer market participant. The authors concluded that ignoring the interest of each agent in the technology transfer market can reduce the synergistic effectiveness of government measures and mechanisms to support the technology transfer process. As a result of the study, the values of the participation of key innovation actors in the technology transfer process were identified.